Ethical based mathematical model to evaluate software engineering - Hameed, Shihab A.; AlJumaily, A. Asad; Ahmed, I. Mohammed; Daoud, Jamal Ibrahim (IDOSI Publication, 2013)
Software engineering techniques and tools are required to develop or build any computer-based applications. The task of developing Software applications is a complex, expensive and ethical engineering which requires qualified software engineering professionally and ethically. Studies and literature denoted that software engineering professionals still facing problems concerning ethical aspects. Analysis shows that Islamic sources (Holy Qur’an and Sunnah) are the highest standard ethical principles for building individual, communities and Ummah (nation) levels. Islamic ethics are universal, stable, comprehensive, fair and standard which are suitable for all nations and times; and when followed leads to create an ethically great society. To effectively solve ethical problem in computer and software engineering field; we propose a new model, which mainly based on integrating an Islamic based solution to solve ethical related problems. This paper focuses on adopting new Ethical Based Mathematical module to evaluate software engineering people and model.